Detection of extended-spectrum beta-lactamases in clinical isolates of Klebsiella pneumoniae and Escherichia coli. - Jacoby, G A (1996)
Forty clinical isolates of Escherichia coli and 141 isolates of Klebsiella pneumoniae that either transferred ceftazidime resistance or showed sulbactam enhancement of oxyimino-beta-lactam susceptibility were tested by disk diffusion methodology for susceptibility to aztreonam, cefotaxime, ceftazidime, and cefoxitin. With standard 30 micrograms antibiotic disks, the fraction of these extended-spectrum beta-lactamase (ESBL)-producing isolates testing resistant by National Committee for Clinical Laboratory Standards criteria was lowest (24%) with cefotaxime disks. Forty percent of the E. coli and 29% of the K. pneumoniae isolates appeared susceptible with at least one oxyimino-beta-lactam disk. Ceftazidime and aztreonam disks were equivalent in differentiating ESBL production, and both were superior to cefotaxime disks. Over half the E. Coli and 29% of the K. pneumoniae isolates tested cefoxitin resistant. In 30 isolates, cefoxitin resistance was transmissible and due to a plasmid-mediated AmpC-type beta-lactamase. With a 5-micrograms ceftazidime disk, a breakpoint could be chosen with high sensitivity and specificity for ESBL-producing organisms. Present disk diffusion criteria underestimate the prevalence of ESBL-producing strains.